Endoscopic submucosal dissection for colorectal neoplasia: outcomes and predictors of recurrence - Maselli, Roberta; Spadaccini, Marco; Belletrutti, Paul J.; Galtieri, Piera Alessia; Attardo, Simona; Carrara, Silvia; Anderloni, Andrea; Fugazza, Alessandro; Ferrara, Elisa Chiara; Pellegatta, Gaia; Iannone, Andrea; Hassan, Cesare; Repici, Alessandro (Endoscopy International Open, 2022)
Background and study aims The role of endoscopic submucosal dissection (ESD) for colorectal lesions in Western communities is unclear and its adoption is still limited. The aim of this study is to assess the long-term outcomes of a large cohort of patients treated with colorectal ESD in a tertiary Western center.Patients and methods A retrospective analysis was conducted on patients treated by ESD for superficial colorectal lesions between February 2011 and November 2019. The primary outcome was the recurrence rate. Secondary outcomes were en-bloc and R0 resection rates, procedural time, adverse events (AEs), and need for surgery. The curative resection rate was assessed for submucosal invasive lesions.Results A total of 327 consecutive patients, median age 69 years (IQR 60–76); 201 men (61.5 %) were included in the analysis. Of the lesions, 90.8 % were resected in an en-bloc fashion. The rate of R0 resection was 83.1 % (217/261) and 44.0 % (29/66) for standard and hybrid ESD techniques, respectively. Submucosal invasion and piecemeal resection independently predicted R1 resections. A total of 18(5.5 %) intra-procedural AEs (perforation:11, bleeding:7) and 12(3.7 %) post-procedural AEs occurred (perforation:2, bleeding: 10). Eighteen adenoma recurrences per 1,000 person-years (15cases, 5.6 %) were detected after a median follow-up time of 36 months. All recurrences were detected within 12 months. No carcinoma recurrences were observed. R1 resection status and intra-procedural AEs independently predicted recurrences with seven vs 150 recurrences per 1,000 person-years in the R0 vs R1 group, respectively.Conclusions Colorectal ESD is a safe and effective option for managing superficial colorectal neoplasia in a Western setting, with short and long-terms outcomes comparable to Eastern studies. En-bloc R0 resection and absence of intra-procedural AEs are associated with reduced risk of recurrence.